Impact of a 12-minute educational video prior to initial consultation in a Mature Women's Health and Menopause Clinic. Issue 7 (July 2022) - Bouteaud, Jeanne; Shaltout, Ola; Christakis, Marie K.; Murtaza, Fahmeeda; Wolfman, Wendy; Shirreff, Lindsay
Abstract: Objectives: Assess acceptability of a 12-minute educational video before menopause clinic consultation and evaluate its impact on knowledge and treatment certainty. Methods: This was a pre-post intervention study among new patients with vasomotor symptoms (VMS) referred to a menopause clinic in Toronto, Canada. Participants completed electronic questionnaires before and after viewing a 12-minute online video covering menopause facts and VMS treatments. Participants' demographic information and referring provider type were recorded. A 19-item true/false knowledge quiz and validated Decision Conflict Scale (DCS) were administered before and after viewing the video along with a validated Acceptability questionnaire after the video. Demographic information and acceptability were summarized descriptively and independent samples t tests compared knowledge and DCS total and subscores before and after viewing the education module. Multivariable analysis was used to identify factors associated with achieving treatment certainty. Results: Seventy-one participants completed pre- and postintervention questionnaires. Mean age was 51.4 ± 6.0 years and most were White (58/71, 81.7%), had a university degree (24/71, 63.3%) and household income >90, 000 (53/71, 74.6%). After the video, there was significant increase in knowledge score (12.7 ± 2.1 vs. 16.9 ± 1.8, P < 0.001) and decrease in all DCS scores (total and five subscores) compared with preintervention scores ( P < 0.001). Acceptability was high with 62/71 (87.3%) respondents indicating the tool was useful. Findings were independent of level of education, household income, and referring physician type. Conclusion: In a study of predominantly university-educated White women, a 12-minute education module on menopause and VMS treatment was acceptable, there was improved knowledge and decision certainty about VMS treatment.